Measuring the distortion of time with relativistic effects in large-scale structure. Issue 1 (13th October 2022) - Sobral Blanco, Daniel; Bonvin, Camille
ABSTRACT: To test the theory of gravity one needs to test, on one hand, how space and time are distorted by matter, and on the other hand, how matter moves in a distorted space–time. Current observations provide tight constraints on the motion of matter, through the so-called redshift-space distortions, but they only provide a measurement of the sum of the spatial and temporal distortions, via gravitational lensing. In this letter, we develop a method to measure the time distortion on its own. We show that the coming generation of galaxy surveys, like the Square Kilometre Array, will allow us to measure the distortion of time with an accuracy of 10–30 per cent. Such a measurement will be essential to test deviations from the ΛCDM model in a fully model-independent way. In particular, it can be used to compare the spatial and temporal distortions of space–time and to unambiguously distinguish between modifications of gravity and dark fifth forces acting on dark matter.